Pengaruh Kualitas Sumber Daya Manusia Dan Pemanfaatan Teknologi Informasi Terhadap Kinerja Karyawan Di PT Digital Media Telematika Lamongan - M. Ilham Al Farizi; Hadi Sunaryo; Eka Farida (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to examine the effect of the quality of human resources and the use of information technology on employee performance at PT Digital Media Telematika Lamongan. The population in this study were all employees at PT Digital Media Telematika Lamongan. The sample in this study was a saturated sample with a total sample of 48 respondents. The research method in this study uses quantitative research with an Explanatory Research approach (Explanatory Research). Based on testing using the analysis of the simultaneous F test, the results of the study show that there is a significant effect between the X variable (quality of human resources and the use of technology) simultaneously on the Y variable (employee performance) in employees at PT Digital Media Telematika Lamongan, and the partial t test results. The research shows that the variable quality of human resources has a positive and significant effect on employee performance at PT Digital Media Telematika Lamongan and the use of information technology has a positive and significant effect on employee performance at PT Digital Media TelematikaLamongan. Keywords: Quality Of Human Resources, Utilization Of Information Technology, Employee Performance.